Regards sur le droit administratif suisse - Issalys, Pierre (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1978)
Looking at Swiss administrative law from a Quebec perspective, this paper outlines some aspects of the Swiss system that provide useful models or references for the discussion and resolution of current issues in Canadian and Quebec administrative law. These issues are identified as (1) the proliferation of independent administrative agencies, and the means to control or at least systematize the growth of such structures ; (2) the desirability and feasibility of enacting general standards of procedure for administrative action ; (3) the simplification of remedies in the field of judicial review of administrative action ; (4) the desirability and feasibility of allocating judicial review powers to a specialized court, either within or outside the Superior Court ; and (5) the desirability and form of a procedure allowing for political intervention in the decision-making process of independent agencies. In the light of these issues, the paper describes the allocation of review functions between administrative and judicial bodies in Swiss federal law. The structure and activity of the Swiss Federal Court (Tribunal fédéral), and especially of the division of the Court that deals with most administrative law cases, are outlined in some more detail. A short historical sketch leads to a discussion of the corresponding features of the law in some of the cantons, and to consideration of the special position given to social security matters in the general scheme of administrative law. The paper then focusses on administrative action itself, commenting on the most significant provisions in the Federal Administrative Procedure Act (Loi fédérale sur la procédure administrative) of 1968. Special attention is paid to the process of review within the administration, up to the level of the federal cabinet (Conseil fédéral). Corresponding provisions in the law of some of the cantons are also briefly discussed. The description of the federal review process is then completed by an outline of the procedure for judicial review of administrative action by the Federal Court (Recours de droit administrative). Finally, notice is again taken of the special position of social security as regards administrative procedure. The paper draws attention, in its concluding part, to the most interesting insights provided by Swiss law into the current problems of Canadian and Quebec administrative law. The growth of administrative tribunals has been brought under control by structural arrangements, especially in the field of social security. The introduction of general standards of procedure has brought greater uniformity and clarity, has emphasized the unity of administrative process including the review phase before administrative or judicial authorities, and has strenghtened the rule of law over government action. The existence of a single procedure to invoke judicial review eases access to the court. While in many cases review by the court is excluded, these exclusions have to be specific, and leave full opportunity for review within the administration, with adequate safeguards provided by the Administrative Procedure Act. Specialization occurs within the Federal Court, and does not involve a rigid separation between judges applying administrative law and judges applying other branches of the law, as in France or Germany. Finally, ultimate political control over certain types of decisions is admitted as a part of life in Swiss federal law, but is at the same time subjected to a quasi-judicial procedure which makes it an acknowledged source of administrative justice.